E-Learning Moodle Usability Evaluation Using the SUS Questionnaire in Higher Education - Ria Andriani; Ahmad Sa'di (Sistemasi: Jurnal Sistem Informasi, 2022)
The COVID-19 pandemic has had a huge impact on all sectors, from health, economy, social, religious to education. A very real impact in the world of education is the policy of the central and local governments to carry out online teaching and learning processes for all educational institutions from kindergartens to universities to break the chain of the spread of covid 19. So that all universities are required to be able to take advantage of various information technologies available has been very developed, one of which is E-Learning, E-Learning is a form of technological development that can be used for electronic-based teaching and learning processes through the internet network. As an effort to realize the campus trend in information technology, ABC University developed an educational platform in the campus environment by maximizing the use of information technology called WASKITA which functions as a support for teaching and learning activities at universities. This study aims to evaluate e-learning to determine the quality of the applications that have been implemented using the System Usability Scale (SUS) questionnaire. The number of respondents in this study were 34 respondents. The evaluation is done by giving tasks according to the features that exist in Waskita so that it can be known what factors must be improved then conducting interviews with users in this case lecturers at ABC College to be able to process any recommendations that will be given to the manager. The results of the usability measurement of E-Learning Moodle accessed at (Waskita.amikom.ac.id) show the average SUS score is 50 which means that the acceptance rate of this E-Learning is at Marginal Low then the adjective value indicates Poor with a grade scale at level E. Users think that Moodle E-Learning is still complicated to use, causing users to consider using E-Learning especially on mobile applications.